РОЗМЕЖУВАННЯ ВОЛЬНОСТЕЙ ВІЙСЬКА ЗАПОРОЗЬКОГО ТА ВІЙСЬКА ДОНСЬКОГО В 40-ві РОКИ XVIII ст. (Zaporizhzhia Historical Review, 2021)
Basing on the published and archival data, the article describes the process of delimitation of freedoms in Zaporozhian Troops and Don Troops during 1740-s; it was determined that the urgent need for the border stipulated the activity of the representative of Zaporozhian Quarters ñ Vasil Kishensky, Colonel of Mius Palanka; it was established that, despite the dissociation, the problem of ìdisputable landsî had not been solved.